First description of a primary SMARCA4-deficient carcinoma of the salivary glands - David Oestreicher; Irina Kostyuchek; Philipp Ströbel; Dirk Beutner; Tobias Dombrowski (Human Pathology Reports)
SMARCA4-deficient neoplasms have been identified in several organs, including the lung, thorax, esophagus and ovary. In some cases, SMARCA4-deficient neoplasms are associated with specific histologic subtypes, such as small cell carcinoma of the ovary, hypercalcemic type (SCCOHT). These tumors are often high-grade and aggressive, with a propensity for early metastasis and poor prognosis. SMARCA4 (also known as BRG1) is a chromatin-remodeling protein that plays an important role in gene expression regulation. SMARCA4 loss results in altered expression of cell cycle regulators and DNA damage response genes, leading to genomic instability and oncogenesis. We describe the first clinical case of a SMARCA4-deficient carcinoma of the salivary glands, found in a rapidly growing parotid lesion. Initially, the tumor had ipsilateral cervical lymph node metastases without any distant metastases. After tumor surgery with total parotidectomy and neck dissection on the left side, adjuvant radiotherapy was performed. Shortly after completion of radiotherapy, re-staging by a CT scan showed metastases at multiple sites. Immunotherapy with a PDL1 inhibitor and additional palliative radiotherapy for the bony metastases was then initiated.